2010
DOI: 10.19030/cier.v3i10.237
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Metacognitive Awareness On Performance Of Students In Chemistry

Abstract: The impact of metacognitive awareness on students’ performance has been examined in the present study. 900 students of grade X participated in the study.  Metacognitive awareness was measured using inventory, while performance of students was measured with the help of researcher made test in the subject of chemistry.  Results indicated that metacognitive awareness was significantly correlated with the performance of students.  The highly metacognitively aware science students performed well on the test.  Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 4 publications
4
17
1
6
Order By: Relevance
“…Hence it can be suggested that developing of metacognition enables students to be successful learners of physics contents. This finding is consistent with some findings from other authors that have done similar researches but not particularly regarding the physics learning (Kruger and Dunning, 1999;Ozsoy & Ataman, 2009;Singh, 2009;Topcu & Yilmaz-Tuzun, 2009;Rahman et al, 2010;Ku and Ho, 2010;Krebs and Roebers, 2012).…”
Section: Correlation Between Level Of Metacognitive Awareness and Stusupporting
confidence: 93%
See 1 more Smart Citation
“…Hence it can be suggested that developing of metacognition enables students to be successful learners of physics contents. This finding is consistent with some findings from other authors that have done similar researches but not particularly regarding the physics learning (Kruger and Dunning, 1999;Ozsoy & Ataman, 2009;Singh, 2009;Topcu & Yilmaz-Tuzun, 2009;Rahman et al, 2010;Ku and Ho, 2010;Krebs and Roebers, 2012).…”
Section: Correlation Between Level Of Metacognitive Awareness and Stusupporting
confidence: 93%
“…For 6 th through 8 th grade students, knowledge of cognition, regulation of cognition, and quick learning contributed to science achievement (Topcu & Yilmaz-Tuzun, 2009). It is shown that metacognitive awareness was significantly correlated with the performance of students in chemistry (Rahman et al, 2010). Ku and Ho (2010) showed that good critical thinkers are engaged in more metacognitive activities.…”
Section: Conception Of Metacognitionmentioning
confidence: 97%
“…12,16 This is also in contradiction with the findings of Imran M et al, Rani R et al, Siddique A et al, and Ul Rehaman F et al who say that gender has no role to play in awareness of metacognition. 13,[17][18][19] One of the plausible reasons for males having better metacognitive awareness than females could be that the areas of the brain related to metacognition is better developed in males, this area being the prefrontal cortex. 20 Our research, also in sync with the above studies, shows better metacognitive awareness scores in males though it is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Someone who reflected or thought back to what he thought was not only good in the understanding of what he knew, but also could make his own decisions to consciously learn to correct mistakes, while Woolfolk explained that the decision-making activity included assessment of the process was generated by thinking and learning outcomes [27]. Research finding by Rahman et.al showed that the activity of reflection was able to increase the learners' metacognition ability [33]. However, the reflection was often not done because learners were less able to manage time during their study.…”
Section: Indicatorsmentioning
confidence: 99%